Job scheduling for dynamic data replication strategy in heterogeneous federation data grid systems - Zarina, Mohamad; Ahmad Nazari, Mohd Rose; Fadhilah, Ahmad (2013)
Data grid technology has the advantage of allowing data sharing and collaboration activities across many organizations in geographically dispersed locations. Due to collaboration activities in distributed data grid, improving data access is one of the issues that need to be wisely addressed in achieving better optimization. In this paper, a replication model for federation data grid system called Sub-Grid-Federation had been proposed to improve access latency by accessing data from an area identified as `Network Core Area' (NCA). The performance of access latency in Sub-Grid-Federation had been tested based on the mathematical proving and simulated using OptorSim simulator. Hence, Sub-Grid-Federation is a better alternative for the implementation of collaboration and data sharing in data grid system.